Availability, coverage, and scope of health information systems for kidney care across world countries and regions - See, Emily J; Bello, Aminu K; Levin, Adeera; Lunney, Meaghan; Osman, Mohamed A; Ye, Feng; Ashuntantang, Gloria E; Bellorin-Font, Ezequiel; Benghanem Gharbi, Mohammed; Davison, Sara; Ghnaimat, Mohammad; Harden, Paul; et al. (Nephrology, dialysis, transplantation, 2021)
BACKGROUND: Health information systems (HIS) are fundamental tools for the surveillance of health services, estimation of disease burden and prioritization of health resources. Several gaps in the availability of HIS for kidney disease were highlighted by the first iteration of the Global Kidney Health Atlas. METHODS: As part of its second iteration, the International Society of Nephrology conducted a cross-sectional global survey between July and October 2018 to explore the coverage and scope of HIS for kidney disease, with a focus on kidney replacement therapy (KRT). RESULTS: Out of a total of 182 invited countries, 154 countries responded to questions on HIS (85% response rate). KRT registries were available in almost all high-income countries, but few low-income countries, while registries for non-dialysis chronic kidney disease (CKD) or acute kidney injury (AKI) were rare. Registries in high-income countries tended to be national, in contrast to registries in low-income countries, which often operated at local or regional levels. Although cause of end-stage kidney disease, modality of KRT and source of kidney transplant donors were frequently reported, few countries collected data on patient-reported outcome measures and only half of low-income countries recorded process-based measures. Almost no countries had programs to detect AKI and practices to identify CKD-targeted individuals with diabetes, hypertension and cardiovascular disease, rather than members of high-risk ethnic groups. CONCLUSIONS: These findings confirm significant heterogeneity in the global availability of HIS for kidney disease and highlight important gaps in their coverage and scope, especially in low-income countries and across the domains of AKI, non-dialysis CKD, patient-reported outcomes, process-based measures and quality indicators for KRT service delivery.
Keywords: průřezové studie; zdravotnické informační systémy; Health Information Systems; Cross-Sectional Studies; chronická renální insuficience; Kidney; lidé; Developing Countries; rozvojové země; Humans; ledviny; Renal Insufficiency, Chronic